Conjunctivitis in the newborn- A comparative study - Meenakshi Wadhwani; Pamela D'souza; Rajesh Jain; Renu Dutta; Arvind Saili; Abha Singh (Wolters Kluwer Medknow Publications, 2011)
Background: Conjunctivitis of the newborn is defined as hyperemia and eye discharge in the neonates and is a common infection occurring in the neonates in the first month of life. In the United States, the incidence of neonatal conjunctivitis ranges from 1-2%, in India, the prevalence is 0.5-33% and varies in the world from 0.9-21% depending on the socioeconomic status. Aim: To study the organisms causing conjunctivitis of the newborn and to correlate the etiology with the mode of delivery. Design: Single center, prospective, observational study. Materials and Methods: A total of 300 mothers and their newborns, born over a period of one year, were included in the study. Of these 200 newborns were delivered through vaginal route (Group A) and 100 (Group B) delivered by lower segment caesarean section (LSCS). At the time of labour, high vaginal swabs were taken from the mothers. Two conjunctival swabs each from both eyes of the newborn were collected at birth and transported to Microbiology department in a candle jar immediately. Results: Eight babies in Group A, developed conjunctivitis at birth. None of the babies in Group B developed conjunctivitis, this difference was statistically highly significant (P<0.000). The organisms found in the conjunctiva of the newborns in Group A were Coagulase negative Staphylococcus, α hemolytic Streptococcus, Escherichia coli and Pseudomonas spps. However, the commonest organism leading to conjunctivitis in the newborn in this study was Coagulase negative Staphylococcus. It was observed that the mothers of 5 out of 8 babies (60%) developing conjunctivitis gave history of midwife interference and premature rupture of membranes so the presence of risk factors contribute to the occurrence of conjunctivitis in the newborn. Conclusions: It is inferred that the mode of delivery and the presence of risk factors is responsible for conjunctivitis in the newborn.